Trans-Neptunian Objects and Comets Saas-Fee Advanced Course 35. Swiss Society for Astrophysics and Astronomy - Jewitt, D.; Morbidelli, A.; Rauer, H. (Saas-Fee Advanced Course, 2008)
In the last two decades of the 20th century, we obtained our first detailed look at a cometary nucleus and detected objects in the Kuiper-Edgeworth Belt for the first time. These two observations have resulted in a major leap forward in our understanding of small bodies in our Solar System. Combined with powerful new approaches to the study of Solar System dynamics, progress within the last 20 years has been staggering. This book attempts to synthesize these new findings in a manner which is readable for new graduate students in the field.